Transformasi Desa Melalui Inovasi Pendidikan dan Kreativitas Mahasiswa KKN: Studi Kasus di Sidang Gunung Tiga, Mesuji - Nur Huda; Maya Fadila Sari (WISE Pendidikan Indonesia, 2024)
The Community Service Program (KKN) in Sidang Gunung Tiga Village, Mesuji Regency, was implemented using participatory, collaborative, and needs-based approaches to promote village transformation through educational and technological innovation. This study aims to describe the impact of the KKN program on youth capacity development, institutional strengthening, environmental awareness, local economic development based on village potential, and student reflection as agents of change. The methods employed include field observation, interviews, Focus Group Discussions (FGDs), training, and program documentation. The results show that KKN students played the role of facilitators, educators, and catalysts for social change through various programs involving digital literacy, entrepreneurship, environmental preservation, and MSME empowerment. SWOT analysis revealed strengths in collaboration and community engagement, as well as challenges in sustainability and limited village infrastructure. The study concludes that the KKN program significantly contributes to creating a sustainable, education-based village development model. Recommendations are directed toward the importance of institutional support, multi-stakeholder collaboration, and post-KKN follow-up to ensure the continuity of the program.